The Strategi Peningkatan Penjaminan Mutu PTKI Pada Direktorat Pendidikan Tinggi Keagamaan Islam Subdit Kelembagaan Dan Kerjasama - Muhamad Hani Yusuf; Muh. Wasith Achadi; Ahmad Mahfud Arsyad (Departement of Mathematics Education, 2024)
The quality of teaching and learning is a primary concern in the global higher education system, including in Indonesia This article highlights the efforts of Islamic religious higher education institutions in ensuring their quality meets established standards Quality assurance in education, as mandated by existing regulations, involves integrated efforts from various parties to enhance the nation's intelligence through education. However, improving the quality of higher education in Indonesia is still a challenge, especially in terms of accreditation results that show most universities are in criteria B and C. This article also discusses strategies and factors that encourage the improvement of higher education quality, focusing on strategies implemented by the Directorate of Islamic Higher Education. The research method uses a qualitative approach with data collection through interviews, observation, and documentation. The results of content and descriptive analysis support propositions and ideas in improving the quality of higher education in Indonesia. The strategies discussed include accreditation assistance and training in the preparation of internal quality assurance documents, as well as the importance of developing strategic plans and renop documents together. Effective implementation of the Renop relies on the clarity and accuracy of the Renstra, emphasizing the importance of both being developed on an ongoing basis. Through coordinated cooperation and internal efforts, it is hoped that universities can continue to improve their quality to support the development of quality education in Indonesia.